Uso de antimicrobiano nanoparticulado para o tratamento da mastite subclínica de ovelhas de corte no período seco - Santana, Raul C.M.; Zafalon, Luiz Francisco; de Brandão, Humberto M.; Junior, Guilherme A.F. [UNESP]; Pilon, Lucas Eduardo [UNESP]; Junior, Waldomiro B.; Giglioti, Rodrigo [UNESP]; Mosqueira, Vanessa Carla F. (FapUNIFESP (SciELO), 2016)
Santana R.C.M., Zafalon L.F., Brandao H.M., Junior G.A.F., Pilon L.E., Junior W.B., Giglioti R. & Mosqueira V.C.F. 2016. [[]Use of nanoparticulated antimicrobians to treat subclinical mastitis of ewes during the dry period.] Uso de antimicrobiano nanoparticulado para o tratamento da mastite subclinica de ovelhas de corte no periodo seco. Pesquisa Veterinaria Brasileira 36(9):826-830. Unidade Pecuaria Sudeste, Embrapa, Rodovia Washington Luiz Km 234 s/n, Caixa Postal 339, Sao Carlos, SP 13560-970, Brazil. E-mail: raul. mascarenhas@embrapa. br Inflammation of the mammary gland is one of the main causes of losses in sheep-rearing. This study aimed to investigate the cure rates from treating subclinical mastitis after intramammary infusion of active antimicrobial agents as conventional formulations or as nanoparticles, at the time when the ewes are being dried off. A total of 584 mammary glands in 307 ewes in meat-producing herds located in Sao Carlos, Sao Paulo, Brazil, were analyzed. Prescreening of subclinical mastitis cases was done using the California mastitis test (CMT) and/or the somatic cell count (SCC). Microbiological analyses were performed to confirm the infectious etiology. The mammary glands with subclinical mastitis were distributed into three groups: G1 (control; mammary glands that did not receive any antimicrobial treatment); G2 (mammary glands to which 100mg of benzathine cloxacillin in conventional form were administered); and G3 (mammary glands to which 50mg of benzathine cloxacillin in nanoparticulate form were administered). The treatment applied to G3 was more efficient (P=0.047) in curing mammary glands with subclinical mastitis. Use of cloxacillin nanoparticles at the time when the ewes are being dried off helps to control infectious subclinical mastitis and reduces consequential losses among meat-producing herds.
Use of nanoparticulated antimicrobians to treat subclinical mastitis of ewes during the dry period